Identification of Intracellular β-Barrel Residues Involved in Ion Selectivity in the Mechanosensitive Channel of Thermoanaerobacter tengcongensis - Song, Yingcai; Zhang, Bing; Guo, Fei; Yang, Maojun; Li, Yang; Liu, Zhi-Qiang (Frontiers in Physiology, 2017)
The mechanosensitive channel of small conductance (MscS) is a bacterial membrane pore that senses membrane tension and protects cells from lysis by releasing osmolytes. MscS is a homoheptameric channel with a cytoplasmic domain with seven portals and a β-barrel opening to the cytoplasm. TtMscS, an MscS channel from Thermoanaerobacter tengcongensis, is an anion-selective channel. A previous study from our laboratory has defined the crucial role of β-barrel in the anion selectivity of TtMscS (Zhang et al., 2012). However, the mechanistic details by which the β-barrel determines anion selectivity remain unclear. Here, using mutagenesis and patch-clamp recordings, we investigated the function and structural correlations between β-barrels and the anion selectivity of TtMscS at the atomic level. Our results indicated that mutation of V274, a residue at the centre of the inner wall of the β-barrel in TtMscS, caused the anion selectivity of TtMscS to reverse to cation selectivity. Moreover, the electrostatic potential (T272) and physical size (L276) of residues in the inner wall of β-barrel also determine the anion selectivity of TtMscS. In summary, the present study confirmed that the β-barrel region of TtMscS acts as a “selective filter” that renders TtMscS anion selective.